Digital Citizenship, Values and Cultural Dynamism - O'Toole, J. Mitchell; Lee, John K.; Altamimi, Taghreed (International Journal of Research in STEM Education, 2024)
This paper examines the global shift towards digital citizenship triggered by COVID-19 and its role in mediating cultural tensions in a rapidly digitizing world. Utilizing mixed methods, the study draws from two projects: the first assesses the engagement of 315 Australian adolescents with values in their science education, and the second investigates digital citizenship practices among 303 university faculty members in Saudi Arabia. The findings highlight significant sociocultural differences in digital engagement and underscore the varying impacts of digital globalization across different educational and national contexts. The paper argues for a proactive educational strategy that encourages critical engagement with digital tools to navigate and reconcile these cultural dynamics effectively. By exploring the interactions between digital technology providers, users, and regulatory bodies, the study provides insights into the complexities of digital responsibility and the potential of education to foster a balanced digital citizenship. This approach suggests moving beyond mere technological integration to embrace a pedagogy that is responsive to the ethical challenges posed by global digital interactions.